Hypothermia for Hypoxic Ischemic Encephalopathy in Infants ≥ 36 weeks - Higgins, Rosemary D. (2009)
Hypoxic ischemic encephalopathy is a serious condition affecting infants which can result in death and disability. This is a summary of pathogenesis of HIE, animal studies of cooling for hypoxic and ischemic models, human hypothermia trials, and the American Academy of Pediatrics publication on hypothermia for HIE. Hypothermia for neonatal HIE is continuing to evolve as a therapy. Studies, gaps in knowledge and opportunities for research are presented herein.